Palmar vertical hemi-hand amputation: A rare form of amputation - Ayhan Okumus (Turkish Journal of Plastic Surgery, 2020)
The patient presented in this study was admitted to our clinic with an uncommon injury as a result of the accidental insertion of his hand in a rope winding machine at a textile factory. A 26-year-old male patient was responsible for the control of a rope wrapping machine at a textile factory. While working, the employee's left hand was injured by making contact with the running machine. He had no problem with the dorsal aspect of his hands, but the volar examination revealed a soft-tissue defect on his wrist flexor line from the pulp level. The defect contained more than the palmar half of the hand's lateral width and all structures were amputated in the impaired manner. The patient was treated with a sensory inguinal flap and two-stage flexor tendoplasty. He is now able to perform routine daily tasks such as hand gripping, holding a pencil, buttoning buttonholes, and dressing.